2017
DOI: 10.12809/hkjr1615395
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic-guided Vacuum-assisted Breast Biopsy in the Asian Population: What Factors Affect Marker Migration?

Abstract: Objective: Stereotactic-guided vacuum-assisted biopsy (VAB) can be performed in small breast masses, distortions, and microcalcifications. A metallic marker is deployed at the corresponding biopsy site to facilitate localisation if additional surgery is required. There is currently limited literature on the accuracy of marker placement in Asian breasts that tend to be smaller and denser than those in Caucasians. The objective of this study was to evaluate the factors that may affect marker migration in stereot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Alternatively, stereotactic-guided vacuumassisted breast biopsy can definitely enable a larger volume of tissue to be obtained although migration can occur of the marker placed at biopsy. To et al4 reported the occurrence of significant marker migration by 1 cm or more in 17% of 153 patients biopsied over a 5-year period that might adversely affect the accuracy of the subsequent surgical localisation procedure. The authors found marker migration was correlated with age, breast compression thickness, number of biopsy cuttings, and duration of the procedure.…”
mentioning
confidence: 99%
“…Alternatively, stereotactic-guided vacuumassisted breast biopsy can definitely enable a larger volume of tissue to be obtained although migration can occur of the marker placed at biopsy. To et al4 reported the occurrence of significant marker migration by 1 cm or more in 17% of 153 patients biopsied over a 5-year period that might adversely affect the accuracy of the subsequent surgical localisation procedure. The authors found marker migration was correlated with age, breast compression thickness, number of biopsy cuttings, and duration of the procedure.…”
mentioning
confidence: 99%